Social fear and its relationship to parental treatment methods among a sample of outstanding students in the province of Damascus - Saada, Mohammed; Sulaitan , Fadi (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
Aim of the research to identify the relationship between social fear and methods of parental treatment in a sample of outstanding students in the province of Damascus, and the know of the differences among a sample search individuals in the social fear and parental treatment methods according to the variables (sex, and number of family members). The sample of the research (452) students from excelling selected purposely from my school (secondary valiant for high achievers in Mezze, and secondary valiant for high achievers in the channels), and dish them Standart social fear and methods of parental treatment and are prepared by the researcher after they were tested for their validity and reliability. The results indicated the following : 1. there is a negative correlation function of a statistical relationship between social fear and methods of treatment with parental outstanding students research sample in the province of Damascus individuals . 2. There were no statistically significant differences between the outstanding students research sample individuals in the social fear, according to the variable sex . 3. There were no statistically significant differences between the academically talented students in the research sample parental treatment methods individuals, according to the variable sex except for the area of ​​interest and sympathy that was the difference in favor of males . 4. no significant statistical differences between the academically outstanding students sample individuals in the social fear and variable according to the number of family members, for the benefit of their families, who consist of (5) person and less . 5. there is significant statistical differences between the academically talented students in the research sample parental treatment methods, according to a variable number of family members, for the benefit of their families, who consist of (5) person and less.